Husband’s ‘Iddah in Indonesian Islamic Law Context: Insights from the Fatwa Approach of the Indonesian Women’s Ulema Congress - Hadi, Mukhammad Nur; Sam'un, Sam'un (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2023)
Islamic family law does not recognize ‘iddah (waiting period) for a husband. However, in Indonesia, he is culturally recommended to postpone remarrying until the completion of his wife's ‘iddah. This article discusses conceptualizing the husband's ‘iddah using the fatwa approach of the Indonesian Women’s Ulema Congress (KUPI). Employing a conceptual and philosophical approach, this article explores secondary data through KUPI's three main fatwa approaches: ma’ruf, mubadalah, and ultimate justice. This article demonstrates that the husband's 'iddah can be deemed obligatory. First, from the ma’ruf perspective, the husband's remarriage during the 'iddah period often harms her due to neglect in providing post-divorce financial support. Second, from a mubadalah standpoint, postponing remarriage after divorce should ideally apply to both husband and wife, allowing psychological reflection space for parties. Third, in the context of ulitimate justice, the husband's remarriage during the ‘iddah period violates the principles of true justice in fulfilling and protecting the rights of women and children. This is because women and children experience more significant and prolonged psychological and social discrimination than men. In this context, mandating ‘iddah for husbands through KUPI's fatwa approach is a pertinent recommendation in Indonesian Islamic legal reform.